Errors and variations of TESL students’ written description - Ahour, Touran; Mukundan, Jayakaran (Universiti Putra Malaysia Press, 2012)
The focus of this study was to highlight different kinds of errors and variations that emerge in the writings of ESL students. The participants of the study were twelve TESL undergraduate students from the Faculty of Educational Studies at Universiti Putra Malaysia. Students’ written descriptions on a picture stimulus were collected and qualitatively analyzed. Then, the emerging errors in their descriptions were categorized into the linguistic and surface structure taxonomies. The findings revealed different grammatical errors in their writings which were basically related to the categories of verb phrases and noun phrases in either simple or compound/complex sentences that resulted in giving misinformation, one of the categories in surface structure. Some variations were also found in the word choice of the students in the three ethnic groups of the study, whereby these choices might be the reflections of their cultural background and world view. The results could help material developers to develop the necessary tasks and exercises and teachers to devise the best teaching strategies for overcoming these kinds of errors in ESL learners’ writings.